Eksplorasi Kesadaran dan Faktor Budaya Keamanan Terhadap Keamanan Informasi Dinas Komunikasi dan Informatika Kabupaten XYZ - Michael Parlindungan (The Indonesian Journal of Computer Science, 2024)
The role of information technology in the government sector is to organize an efficient, accountable, and transparent electronic government system. The human aspect is the weakest and plays the most important role in maintaining information security. The XYZ District and Communication Agency is important in organizing regional government, including information system management and information security. This study measured the level of information security awareness of 86 employees at the XYZ District Kominfo Agency using a questionnaire based on the HAIS-Q method and aspects of information security culture. The results showed that the level of employee security awareness was at the "average" level. The areas of password management, email, and internet use showed a "poor" level of awareness, and the use of social media, mobile devices, information handling, and incident reporting was at the "average" level. The security culture aspect also influenced the level of employee security awareness which was at the "average" level. Based on the results, recommendations for increasing awareness are needed, such as the creation of information security policies and guidelines, and the implementation of information security awareness programs.